The Effectiveness Of Stem-Arnutri Approach In Improving Secondary School Students’ Knowledge, Attitudes And Behaviour Towards Nutrition - Kalimuthu, Ilavarasi (2024)
Nutrition is a critical part of both health and development and holds a prominent place in the educational agenda in malaysia. Proficient and wellstructured nutrition education has the potential to enhance students’ ability to grasp the knowledge towards nutrition, visualize the abstract concept, and promote good health and wellbeing, which can prevent non-communicable diseases (ncd’s) in the long run. This mixed-methods intervention study aimed to create a more effective nutrition education approach based on current practices. The first level of the study investigated the existing teaching and learning practices concerning nutrition topics among secondary school students and teachers. The sample for level 1 comprises six experienced lower secondary science teachers and seven students who have studied the topic of nutrition. Qualitative insights gathered during this level served as the foundation for developing nutrition instruction in level two. The integration of science, technology, engineering, and mathematics (stem) with augmented reality (ar) mobile applications led to the formulation of the stem-arnutri teaching and learning approach. During the third level, the study evaluated how the stem-arnutri teaching and learning approach influenced the knowledge, attitudes, and behaviors of form two students in relation to nutrition. This assessment employed a quasi-experimental design, specifically a non-equivalent pre- and posttest control group design.